A Review of Peer Relationships and Friendships in Youth With ADHD. (October 2015) - Gardner, Denise M.; Gerdes, Alyson C.
Objective: The purpose of this essay is to examine peer relationships in youth with ADHD and to review current peer functioning interventions.Method: The studies included in this review were identified using the following search terms: "attention-deficit/hyperactivity disorder, " "ADHD, " "peer relationships, " "friendships, " "social skills, " "intervention, " and "treatment." Other than a few seminal studies published prior to 2000, studies included were published between 2000 and 2012.Results/Discussion: Background information regarding peer relationship difficulties and specific social skills deficits of youth with ADHD is reviewed and current social skills and friendship intervention programs are examined. Future directions also are provided.